Anti-atherogenic and cardio-protective properties of sweet melon (Cucumis melo. L. Inodorus) seed extract on high fat diet induced obesity in male wistar rats - G. Adebayo-Gege; V. Alicha; T. O. Omayone; S. C. Nzekwe; C. A. Irozuoke; O. A. Ojo; A. F. Ajayi (BMC, 2022)
Abstract Background Cucumis melon is a medicinal plant with multiple pharmacological properties such as anti-inflammatory, antioxidant, and diuretic effects. An increasing body of scientific evidence established the anti-diabetic/anti-obesity effects of Cucumis melo in humans, mice, and hamster models. However, there are no tangible reports on its ability to prevent cardiovascular complications following diet-induced obesity. The anti-atherogenic and cardioprotective effects of the Methanolic extract of Cucumis melo. L. Inodorus seeds on a high-fat diet (HFD)-induced obese rats was assessed in this study.  Methods Forty male Wistar rats were randomly divided into five groups, (n = 8/group); i.e., Normal (N), HFD, HFD + 50 mg/kg b.w. of MCMs (Methanolic extract of Cucumis melon seeds), HFD + 100 mg/Kg b.w. of MCMs and HFD + 200 mg/kg b.w. of MCMs. The experimental animals were anaesthetized and sacrificed after 10 weeks, and blood samples and heart tissue were collected for further analysis. Using the Graph Pad Prism version 5.0, the results expressed as Mean ± SD was tested using the one-way ANOVA to show intergroup differences, followed by Bonferonni 's post hoc test. The level of significance was determined at P ≤ 0.05. Results MCMs significantly (P < 0.05) reduced body weight, adiposity index, total fat mass, low-density lipoprotein cholesterol (LDL-c), and total cholesterol (TC) compared with the HFD obese groups MCMs caused a significant reduction in the body weight, total fat mass, adiposity index, low-density lipoprotein cholesterol (LDL-c), and total cholesterol (TC) when compared to the animals in HFD obese groups. Also, the Atherogenic index of plasma (AIP), Castelli index and, malondialdehyde (MDA) significantly (P < 0.05) decreased in MCMs treated groups compared to the HFD obese group. The catalase, protein, and HDL levels were significantly increased in MCMs treated groups compared to HFD-obese animals. Expression of nitric oxide in the form of nitrite in the heart tissue significantly increased in the MCMs treated compared to the HFD-obese rats, with the majority of the positive results recorded at 100 mg/Kg b.w. of MCMs. Conclusions MCMs have anti-atherogenic and Cardio-protective properties on High Fat Diet-Induced Obesity in Male rats via an antioxidant and nitric oxide-dependent mechanism. Further study is recommended to evaluate the molecular mechanisms to which these anti-atherogenic and cardio-protective actions can be attributed and exploit the GCMS result in the development of drug candidates.